Metamorphic InAs(Sb)/InGaAs/InAlAs nanoheterostructures grown on GaAs for efficient mid-IR emitters. Issue 1 (February 2019) - Ivanov, S.V.; Chernov, M.Yu.; Solov'ev, V.A.; Brunkov, P.N.; Firsov, D.D.; Komkov, O.S.
Abstract: High-efficiency semiconductor lasers and light-emitting diodes operating in the 3–5 μm mid-infrared (mid-IR) spectral range are currently of great demand for a wide variety of applications, in particular, gas sensing, noninvasive medical tests, IR spectroscopy etc. III-V compounds with a lattice constant of about 6.1 Å are traditionally used for this spectral range. The attractive idea to fabricate such emitters on GaAs substrates by using In(Ga, Al)As compounds is restricted by either the minimum operating wavelength of ∼8 μm in case of pseudomorphic AlGaAs-based quantum cascade lasers or requires utilization of thick metamorphic In x Al1 -x As buffer layers (MBLs) playing a key role in reducing the density of threading dislocations (TDs) in an active region, which otherwise result in a strong decay of the quantum efficiency of such mid-IR emitters. In this review we present the results of careful investigations of employing the convex-graded In x Al1 -x As MBLs for fabrication by molecular beam epitaxy on GaAs (001) substrates of In(Ga, Al)As heterostructures with a combined type-II/type-I InSb/InAs/InGaAs quantum well (QW) for efficient mid-IR emitters (3–3.6 μm). The issues of strain relaxation, elastic stress balance, efficiency of radiative and non-radiative recombination at T  = 10–300 K are discussed in relation to molecular beam epitaxy (MBE) growth conditions and designs of the structures. A wide complex of techniques including in-situ reflection high-energy electron diffraction, atomic force microscopy (AFM), scanning and transmission electron microscopies, X-ray diffractometry, reciprocal space mapping, selective area electron diffraction, as well as photoluminescence (PL) and Fourier-transformed infrared spectroscopy was used to study in detail structural and optical properties of the metamorphic QW structures. Optimization of the growth conditions (the substrate temperature, the As4 /III ratio) and elastic strain profiles governed by variation of an inverse step in the In content profile between the MBL and the InAlAs virtual substrate results in decrease in the TD density (down to 3 × 10 7  cm −2 ), increase of the thickness of the low-TD-density near-surface MBL region to 250–300 nm, the extremely low surface roughness with the RMS value of 1.6–2.4 nm, measured by AFM, as well as rather high 3.5 μm-PL intensity at temperatures up to 300 K in such structures. The obtained results indicate that the metamorphic InSb/In(Ga, Al)As QW heterostructures of proper design, grown under the optimum MBE conditions, are very promising for fabricating the efficient mid-IR emitters on a GaAs platform.